2021
DOI: 10.21608/aujes.2021.66918.1014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of ZnS Nanoparticles by Chemical Precipitation Method

Abstract: Nanoparticles form a connection between molecular and bulk states of matter, it shows size-dependent physical and chemical properties. In the present work, we aimed to prepare zinc sulfide (ZnS) nanoparticles by chemical precipitation method using Sodium sulfide (Na2S.x H2O) as sulfur source and zinc acetate dihydrate [(CH3COO)2Zn.2H2O] as a source of zinc. Characterization was performed by UV-Vis Spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectra (FTIR), and transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Transmission electron microscopy (TEM) confirmed the spherical morphology of ZnS nanoparticles with 7.9 nm average particle size. 119 Zhang et al 114 reported synthesis of ZnS/Ni 3 S 2 composite electrode material using a straightforward self-template method. Chemical precipitation (Figure 8) of the Zn−Ni precursor in a polyvinylpyrrolidone (PVP)/Milli-Q water mixture resulted to ZnS/Ni 3 S 2 by thioacetamide (TAA), used as sulfur source.…”
Section: Synthesis Methods For Znsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy (TEM) confirmed the spherical morphology of ZnS nanoparticles with 7.9 nm average particle size. 119 Zhang et al 114 reported synthesis of ZnS/Ni 3 S 2 composite electrode material using a straightforward self-template method. Chemical precipitation (Figure 8) of the Zn−Ni precursor in a polyvinylpyrrolidone (PVP)/Milli-Q water mixture resulted to ZnS/Ni 3 S 2 by thioacetamide (TAA), used as sulfur source.…”
Section: Synthesis Methods For Znsmentioning
confidence: 99%
“…Due to the swift rate of precipitation, it is difficult to control the morphology of produced samples. 12 Ebnelwaled et al 119 studied the synthesis of ZnS nanoparticles through chemical precipitation using zinc nitrate hexahydrate (Zn(NO 3 ) 2 •6H 2 O) as a zinc source and sodium sulfide (Na 2 S•H 2 O) as the sulfur source. XRD revealed ZnS nanoparticles having cubic phase with an average crystallite size of 6.41 nm.…”
Section: Synthesis Methods For Znsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the particle reaches nano-meter size, quantum effects come into play and the effective band gap increases. Increasing bandgap energies of PbS nanoparticles could be evidence of the quantum confinement effect due to decreasing size of structures" [14,15].…”
Section: Optical Analysis Of Pbs Nanoparticlesmentioning
confidence: 99%
“…Due of its multifaceted applications, this particular topic has garnered significant attention from researchers particularly in the field of optical sensors and coating, infrared window, reflector, dielectric filter, solar cells, etc. [4][5][6].…”
Section: Introductionmentioning
confidence: 99%